Development of ripple filter composed of metal mesh for charged-particle therapy. (7th July 2022) - Tanaka, Sodai; Inaniwa, Taku; Matsuba, Shunya
Abstract: Objective. In charged-particle therapy, a ripple filter (RiFi) is used for broadening the Bragg peak in the beam direction. A conventional RiFi consists of plates with a fine ridge and groove structure. The construction of the RiFi has been a time-consuming and costly task. In this study, we developed a simple RiFi made of multi-layered metal mesh (mRiFi), with which the Bragg peak is broadened due to structural randomness, similar to what occurs for the already proposed RiFi with porous material. Approach . The mRiFi was constructed by stacking commercially available metal meshes at random positions and angles. The mRiFi was inexpensive to fabricate due to its high availability and low machining accuracy. The Bragg peak width modulated by the mRiFi can be uniquely determined by the wire material, wire diameter, wire-to-wire spacing of the metal mesh, and the number of mesh sheets. We fabricated four mRiFis consisting of 10, 20, 30, and 40 layers of stainless steel meshes with a wire diameter of 0.1 mm and a wire-to-wire spacing of 0.508 mm. Main results. Using the mRiFis consisting of 10, 20, 30, and 40 mesh sheets, we succeeded in broadening the Bragg peak following the normal distribution with the respective standard deviation σ values of 0.83, 1.15, 1.41, and 1.56 mm in water in experimental planar-integrated depth dose measurements with 140.3 MeV u −1 carbon-ion beams. The effect of range broadening with the mRiFi was independent of its lateral position, and the measurement of the surface dose using radiochromic films showed no severe inhomogeneity with a homogeneity index greater than 0.3 caused by the mRiFis. Significance. The developed mRiFi can be used as a RiFi in charged-particle therapy. The mRiFi has three advantages: high supply stability of the material for manufacturing it, easy fabrication, and low cost.